A novel multi-ingredient supplement significantly improves ocular symptom severity and tear production in patients with dry eye disease: results from a randomized, placebo-controlled clinical trial - Gioia, Neda; Gerson, Jeffry; Ryan, Robert; Barbour, Krista; Poteet, Julie; Jennings, Brooke; Sharp, Matthew; Lowery, Ryan; Wilson, Jacob; Morde, Abhijeet; Rai, Deshanie; Padigaru, Muralidhara; et al. (Frontiers in Ophthalmology, 2024)
IntroductionDry eye disease (DED) is multifactorial and characterized by a loss of tear film homeostasis that causes a cycle of tear film instability, tear hyperosmolarity, and inflammation. While artificial tears are the traditional mainstay of treatment, addressing the underlying pathophysiology could relieve symptoms and prevent progression. Increasing evidence indicates a role for oral nutritional supplementation in multiple ophthalmic diseases, including DED. Lutein, zeaxanthin, curcumin, and vitamin D3 have demonstrated protective and anti-inflammatory properties in ocular models. This prospective, randomized, double-blind, parallel, placebo-controlled study evaluated the efficacy and safety of a proprietary blend of lutein, zeaxanthin isomers, curcumin, and vitamin D3 (LCD) as a daily supplement in adult participants with DED.MethodsParticipants were randomized to receive one LCD supplement capsule (lutein 20 mg, zeaxanthin isomers 4 mg, curcumin 200 mg curcuminoids, and vitamin D3 600 IU) or placebo per day for 8 weeks (LCD, n=77; placebo, n=78). Primary outcomes were changes in tear volume (Schirmer’s test) and ocular symptoms (Ocular Surface Disease Index [OSDI]).ResultsThe study met its primary endpoints: the LCD group demonstrated significantly better Schirmer’s test scores and improvement in overall OSDI score, versus placebo, at Day 56 (p<0.001 for both). Scores for total OSDI, and symptoms and vision domains, significantly improved by Day 14 for LCD versus placebo, (p<0.05 for all) and were maintained to Day 56 (p<0.001). In addition, the LCD group demonstrated significantly improved tear film break-up time (TBUT) and tear film osmolarity, versus placebo, by Day 56 (p<0.001), along with significant improvements in corneal and conjunctival staining (p<0.001 for both), and inflammation (matrix metalloproteinase-9; p<0.001 for each eye). Total Standard Patient Evaluation of Eye Dryness (SPEED) score, and scores for the frequency and severity domains, were significantly improved by Day 14 for LCD versus placebo (p<0.05 for all) and maintained to Day 56 (p<0.001). There was no difference between groups for artificial tear usage. The supplement was well-tolerated.DiscussionOnce-daily LCD supplementation significantly improved tear production, stability and quality, reduced ocular surface damage and inflammation, and improved participants’ symptoms. LCD supplementation could offer a useful adjunct to artificial tears for patients with DED (NCT05481450).